2019
DOI: 10.1002/job.2354
|View full text |Cite
|
Sign up to set email alerts
|

Are servant leaders appreciated? An investigation of how relational attributions influence employee feelings of gratitude and prosocial behaviors

Abstract: Summary Multisource data collected at three time phases were used in investigating when servant leadership elicits gratitude and then promotes prosocial behaviors. We tested a moderated mediation model, contending that relational attributions moderate the relationship between servant leadership and gratitude, and then gratitude sequentially predicts interpersonal citizenship behaviors and upward voice. As hypothesized, when employees do not highly rely on relational attributions for servant leadership, they fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 73 publications
2
57
0
1
Order By: Relevance
“…Support managers' service can be particularly useful to line managers because support managers' work typically focuses on dealing with administrative, relational, or technical issues that could significantly burden the line managers, whose main focus is on business operations. In this regard, Sun, Liden, and Ouyang (2019) showed that servant leadership leads to positive outcomes by increasing gratitude in followers. Support managers' servant leadership might also enhance line managers' ability to exhibit servant leadership.…”
Section: The Trickle Effects Emanating From the Servant Leadership Ofmentioning
confidence: 99%
“…Support managers' service can be particularly useful to line managers because support managers' work typically focuses on dealing with administrative, relational, or technical issues that could significantly burden the line managers, whose main focus is on business operations. In this regard, Sun, Liden, and Ouyang (2019) showed that servant leadership leads to positive outcomes by increasing gratitude in followers. Support managers' servant leadership might also enhance line managers' ability to exhibit servant leadership.…”
Section: The Trickle Effects Emanating From the Servant Leadership Ofmentioning
confidence: 99%
“…In the first paper, Sun, Liden, and Ouyang () examine a moderated mediation model of the indirect effect of servant leadership on upward voice through gratitude and organizational citizenship behavior toward individuals, conditional upon relational attributions. Sun et al tested their model with multisource data collected from 137 Chinese social workers and their leaders across three phases.…”
Section: An Overview Of the Papers In This Special Issuementioning
confidence: 99%
“…Altogether, these five papers extend attribution theory in numerous areas of critical importance, including micro contexts and macro contexts in organizational behavior, leadership, human resource management, and strategic management. The varying study designs used across Munyon et al's (), Hewett et al's (), and Sun et al's () papers illuminate the myriad of opportunities to empirically examine attributions. Additionally, the cross‐cultural findings from employee respondents in organizations located in China, Great Britain, and the United States show that attributions apply to a range of contexts.…”
Section: An Overview Of the Papers In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between organizational resources and employee outcomes has been a frequent topic in several research streams, including recent works in the organizational behavior literature (Sun et al, 2019;Verma, 2019), organizational communication literature (AL-Hashimi and Al-Barri, 2018;Men and Yue, 2019) and the FLE management literature (Ford et al, 2018;Grant and Wrzesniewski, 2010;Stegen and Wankier, 2018). For example, works based on the job demands-resources theory (JD-R) in the organizational behavior literature have identified core job resources (e.g.…”
Section: Introductionmentioning
confidence: 99%